2020
DOI: 10.1186/s13023-020-1309-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics in patients with hereditary amyloidosis with Glu54Gln transthyretin identified in the Romanian population

Abstract: Background: In Romania, 23 patients have been diagnosed with hereditary transthyretin amyloidosis (ATTRh), 18 of whom have the Glu54Gln mutation. This retrospective cohort included all patients with Glu54Gln-mutated ATTRh who were diagnosed in Romania from 2005 to 2018. Results: Of 18 patients, 10 were symptomatic, five were asymptomatic carriers and three died during the study. All originated from NorthEast Romania. Median age at symptom onset was 45 years; median age at death was 51 years. All patients had c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“…In Romania, a specific mutation with regional distribution for ATTRv (Glu54Gln) was discovered a decade ago [ 31 ] and fully characterized more recently [ 32 ]. In the latest publication the authors stated 23 patients have been diagnosed with ATTRv in Romania, 18 of whom had the Glu54Gln mutation which is characterized by early disease onset, mixed phenotype (both cardiac and neurological involvement), aggressive disease progression and short survival [ 32 ]. Another important finding was that all these 18 patients have origins in the North-Eastern region of Romania (Suceava County) where a cluster of ATTRv patients has been identified [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Romania, a specific mutation with regional distribution for ATTRv (Glu54Gln) was discovered a decade ago [ 31 ] and fully characterized more recently [ 32 ]. In the latest publication the authors stated 23 patients have been diagnosed with ATTRv in Romania, 18 of whom had the Glu54Gln mutation which is characterized by early disease onset, mixed phenotype (both cardiac and neurological involvement), aggressive disease progression and short survival [ 32 ]. Another important finding was that all these 18 patients have origins in the North-Eastern region of Romania (Suceava County) where a cluster of ATTRv patients has been identified [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the latest publication the authors stated 23 patients have been diagnosed with ATTRv in Romania, 18 of whom had the Glu54Gln mutation which is characterized by early disease onset, mixed phenotype (both cardiac and neurological involvement), aggressive disease progression and short survival [ 32 ]. Another important finding was that all these 18 patients have origins in the North-Eastern region of Romania (Suceava County) where a cluster of ATTRv patients has been identified [ 32 ]. They also reported a prevalence of ATTRv of 1.02 per 1,000,000 people in the general Romanian population with 2.39 per 100,000 people in Suceava County and stated that prevalence of this disease in Romania is substantially underestimated due to several factors, including lack of access to or refusal to receive medical care and limited survival of these patients [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, contrary to common belief, CA is no longer considered a rare disease. In Romania, a specific mutation with regional distribution for ATTRv (Glu54Gln) was discovered a decade ago [17] and fully characterized more recently [18]. Moreover, recent studies revealed that ATTRwt can even be considered a common disease, but its prevalence remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…These symptoms often are attributed to other population-prevalent cardiovascular risk factors resulting in underestimation of the clinical penetrance of the Val122Ile 6 . The estimated age of onset for non-cardiac precursor phenotypes for hereditary transthyretin amyloidosis is between 30 to 40 years of age 7 . In two retrospective studies, carpal tunnel syndrome preceded hereditary transthyretin amyloidosis diagnosis by 9-10 years 8,9 .…”
Section: Introductionmentioning
confidence: 99%